2017
DOI: 10.1108/pr-11-2015-0293
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effects of corporate social responsibility and ethical leadership on turnover intention

Abstract: Purpose The purpose of this paper is to apply the self-concept theory and conservation of resources theory to develop a model that explains how both corporate social responsibility (CSR) and ethical leadership influence turnover intention through work engagement and burnout. Design/methodology/approach A survey of employees from banking industry in Taiwan and the research hypotheses were empirically tested by two-step structural equation modeling (SEM) and regression analysis. Findings The empirical findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(120 citation statements)
references
References 140 publications
(114 reference statements)
7
102
0
11
Order By: Relevance
“…This is astonishing, since talent attraction, employee loyalty, and employee productivity can lead to a company's competitive advantages. Albeit scholars have shown greater interest in the individual-level (or employees) CSR literature [7,21], most articles are concerned with the effects of CSR perceptions on employee outcomes such as employee motivation [22], employee engagement [23,24], and employee turnover intention [25]. Employees create value for enterprises; thus, enterprises must perform social responsibility for employees [9,26].…”
Section: Social Responsibility Toward the Employeesmentioning
confidence: 99%
“…This is astonishing, since talent attraction, employee loyalty, and employee productivity can lead to a company's competitive advantages. Albeit scholars have shown greater interest in the individual-level (or employees) CSR literature [7,21], most articles are concerned with the effects of CSR perceptions on employee outcomes such as employee motivation [22], employee engagement [23,24], and employee turnover intention [25]. Employees create value for enterprises; thus, enterprises must perform social responsibility for employees [9,26].…”
Section: Social Responsibility Toward the Employeesmentioning
confidence: 99%
“…Literatürde etik liderlik davranışlarının SS ve KSS algısına pozitif yönde etki ettiğini belirten çalışmalar bulunmaktadır (Lin ve Liu, 2017;Brammer ve arkadaşları, 2007;Lawton ve Paez, 2014;De Roeck ve Farooq, 2018 Giacalone ve Thompson (2006) ise işletmeyi temele alan dünya görüşüne göre materyalist düşüncenin ve kişisel çıkarların karar alma süreçlerine dahil edilmesinin uygun olduğunu belirtmektedir. Dolayısıyla literatüre göre materyalist eğilim algısının KSS algısına pozitif ve negatif etkileri olduğu belirtilebilir.…”
Section: şEkil 1: Araştırma Modeliunclassified
“…Recently, [4,20] found that turnover intention has positive relationship with job stress. Researchers also suggested that inadequate information about the roles and responsibility, unclear expectation of co-worker and top management, extensive job pressure and high of role ambiguity will leads to low employees' belongingness.…”
Section: Job Stress and Turnover Intentionmentioning
confidence: 99%
“…If the employee is engaged with their work, they have the tendency to have good responses such as elated, fun and excited towards their work, resulting less or far away to have turnover intention. In prior study done by [20] have indicated that when employee have lacking amount of the resources, they probably allocate themselves to work with mental resilience and psychological resources such as energy and mental effort, thus decreasing their retention effort. Further, they also found that turnover intention has negative relationship with work engagement.…”
Section: Work Engagement and Turnover Intentionmentioning
confidence: 99%
See 1 more Smart Citation